204k views
5 votes
F(x) = 3x - 2 and g(x) = 2x
Find g(f(3))

User Aritroper
by
5.6k points

2 Answers

0 votes

Answer:

f(3)=7 g(3)=6

Explanation:

f(x)=3x-2

f(3)=3(3)-2

f(3)=9-2

f(3)=7

g(x)=2x

g(3)=2(3)

g(3)=6

User Yiannis Gkoufas
by
4.9k points
2 votes

Answer:

14

Explanation:

To find g(f(3)), you will need to first find f(3) and then substitute that value into the function g(x).

To find f(3), substitute 3 for x in the equation for f(x):

f(3) = 3(3) - 2 = 9 - 2 = 7

Now substitute the value of f(3) into the equation for g(x):

g(f(3)) = g(7) = 2(7) = 14

Therefore, g(f(3)) = 14

User Andrew Martin
by
4.8k points